Analisis Penerimaan Aset Tetap dan Kontribusinya terhadap Pendapatan Asli Daerah (PAD) Studi Kasus pada Pantai Lasiana Kupang (Jurnal Kendali Akuntansi, 2025)
Yohanes N. Gela Loy, NIM 33120041, Thesis entitled "Analysis of Fixed Asset Revenue and Its Contribution to Local Original Income (PAD): Case Study at Lasiana Beach Kupang". Under the guidance of Mrs. Maria Goreti Malut as the first supervisor and Mr. Antonius Y.W. Timuneno as the second supervisor. The problem raised in this study is how fixed asset revenue from the Lasiana Beach Kupang tourist area can contribute to increasing Local Original Income (PAD). The purpose of this study is to analyze the extent to which the utilization of fixed assets owned and managed by the East Nusa Tenggara Provincial Government can contribute significantly to PAD. This study uses a qualitative method with primary and secondary data sources. Data collection techniques were carried out through interviews with the NTT Provincial Tourism Office as well as documentation of financial reports and PAD revenue targets for 2021–2023. The results of the study indicate that although there has been an increase in revenue every year, its contribution to PAD has not been optimal. This is caused by several factors, including: damage to facilities such as stalls and sales stalls, minimal tourism promotion, and lack of supporting facilities. Therefore, to increase the contribution of fixed assets to PAD, infrastructure improvements, increased tourism promotion capacity, and strategic cooperation with the private sector are needed so that asset management can run effectively and sustainably.